PENGARUH PERMAINAN TRADISIONAL TERHADAP PENINGKATAN KEBUGARAN JASMANI - Anggono, Dani Tri; Nurhidayat, Nurhidayat (Universitas Hamzanwadi, 2024)
This study aims to examine the improvement of physical fitness through traditional games. The design used in this research is quasi experiment. The population in this study were 4th and 5th grade students. The subjects of this study were 20 students. Data collection using the TKJI test for ages 9-10 years. Data analysis techniques using t-test analysis, through prerequisite tests of normality and homogeneity. The results of hypothesis testing using paired samples T-tests. The results of the paired samples t-test statistical analysis of the traditional game control group have a sig value of 0.1111 > 0.05, meaning that the traditional game exercise control group has no significant difference between the initial variable and the final variable. While the traditional game exercise of the Experimental Group has a sig value of 0.001 < 0.05 so that it can be interpreted that there is a significant difference between the initial variable and the final variable. It is concluded that the traditional game exercises of the control group did not increase, while the traditional game exercises of the experimental group increased significantly, the increase was initially 12.70 increased to 14.40 the amount of increase was 1.7.